Effect of The Teams Games Tournament Method on Arabic Writing Skills of Student Islamic Junior High School 25 Jakarta - Setiadi, Syamsi; Jannah, Eni Nurul; Zulharby, Puti; Ilham, Andri (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2024)
This research is motivated by the condition of students who have difficulty writing Arabic in Islamic Junior High School students and the need to apply learning methods that are in accordance with the expected competencies. This study aims to determine the influence of the Teams Games Tournament learning method on students' Arabic writing ability. This study is an experimental research with a quasi-experimental design type of experimental group design consisting of 31 students and a control group consisting of 27 students. The sampling technique was carried out by cluster sampling. The data analysis technique used to determine the effect of the independent variable on the bound variable is the t-test. The results showed that t count = 2.52 with a significance of 0.007 lower than 0.05. Thus, it was concluded that there was an influence of the Team Game Tournament method on Arabic writing skills in Islamic Junior High School 25 Jakarta students.